Implementation of the Class 7 Teaching Campus Program in Increasing Students' Interest in Literacy and Numeracy - Wati, Yulia Ambar; Siswoyo, Andika Adinanda (JUPE : Jurnal Pendidikan Mandala, 2024)
One of the independent learning programs organized by the Ministry of Education and Culture is the Teaching Campus. The aim of this research is to implement various campus teaching programs for grade 7 so that students' interest in literacy and numeracy increases. Data collection in this research used qualitative descriptive methods using observation, interviews and documentation. This research was conducted at SMPN 2 Ploso over a period of 4 months. The target of this research is grade 7 students. The results of the research show that the Teaching Campus program such as teaching assistance, the use of the words traffic and touch me as learning media, the application of watching educational films (NOKASI), and the existence of technological adaptation are able to improve students' learning abilities. interest in literacy and numeracy. However, there are still challenges in its implementation, especially in terms of classroom conditioning.Kata Kunci:Kampus Mengajar, Literasi, Numerasi